Robust multimodal cognitive load measurement. ([2016]) - (Researcher on machine learning), Chen, Fang; Zhou, Jianlong; (Researcher on machine learning), Wang, Yang; (Researcher on human-computer interaction), Yu, Kun; Arshad, Syed Z; Khawaji, Ahmad; (Researcher on human-machine systems), Conway, Dan
No abstract available